root 2 minus root 3 upon 3 root 2 minus 2 root 3
Answers
Answered by
9
Hii friend,
✓2 - ✓3 / 3✓2 - 2✓3
=> ✓2-✓3/3✓2 -2✓3 × 3✓2+2✓3/3✓2+2✓3
=> (✓2-✓3)(3✓2+2✓3)/(3✓2 - 2✓3)(3✓2+2✓3)
=> ✓2(3✓2+2✓3)-✓3(3✓2+2✓3)/(3✓2)²-(2✓3)²
=> 3×2 + 2✓6 -3✓6 - 2 × 3/ 18 - 12
=> 6+2✓6-3✓6-6/6
=> -✓6/6 ......Ans.....
HOPE IT WILL HELP YOU..... :-)
✓2 - ✓3 / 3✓2 - 2✓3
=> ✓2-✓3/3✓2 -2✓3 × 3✓2+2✓3/3✓2+2✓3
=> (✓2-✓3)(3✓2+2✓3)/(3✓2 - 2✓3)(3✓2+2✓3)
=> ✓2(3✓2+2✓3)-✓3(3✓2+2✓3)/(3✓2)²-(2✓3)²
=> 3×2 + 2✓6 -3✓6 - 2 × 3/ 18 - 12
=> 6+2✓6-3✓6-6/6
=> -✓6/6 ......Ans.....
HOPE IT WILL HELP YOU..... :-)
Answered by
2
Heya !!
Here's your answer.. ⬇⬇
![= \frac{ \sqrt{2} - \sqrt{3} }{3 \sqrt{2} - 2 \sqrt{3} } \\ \\ = \frac{ \sqrt{2} - \sqrt{3} }{3 \sqrt{2} - 2 \sqrt{3} } \times \frac{3 \sqrt{2} + 2 \sqrt{3} }{3 \sqrt{2} + 2 \sqrt{3} } \\ \\ = \frac{ \sqrt{2}(3 \sqrt{2} + 2 \sqrt{3} ) - \sqrt{3}(3 \sqrt{2} + 2 \sqrt{3} ) }{ ({3 \sqrt{2} }^{2}) - ( {2 \sqrt{3} }^{2}) } \\ \\ = \frac{6 + 2 \sqrt{6} - 3 \sqrt{6} - 6 }{18 - 12} \\ \\ = \frac{ - \sqrt{6} }{6} \\ \\ = \frac{ \sqrt{2} - \sqrt{3} }{3 \sqrt{2} - 2 \sqrt{3} } \\ \\ = \frac{ \sqrt{2} - \sqrt{3} }{3 \sqrt{2} - 2 \sqrt{3} } \times \frac{3 \sqrt{2} + 2 \sqrt{3} }{3 \sqrt{2} + 2 \sqrt{3} } \\ \\ = \frac{ \sqrt{2}(3 \sqrt{2} + 2 \sqrt{3} ) - \sqrt{3}(3 \sqrt{2} + 2 \sqrt{3} ) }{ ({3 \sqrt{2} }^{2}) - ( {2 \sqrt{3} }^{2}) } \\ \\ = \frac{6 + 2 \sqrt{6} - 3 \sqrt{6} - 6 }{18 - 12} \\ \\ = \frac{ - \sqrt{6} }{6} \\ \\](https://tex.z-dn.net/?f=+%3D++%5Cfrac%7B+%5Csqrt%7B2%7D++-++%5Csqrt%7B3%7D+%7D%7B3+%5Csqrt%7B2%7D+-+2+%5Csqrt%7B3%7D++%7D++%5C%5C++%5C%5C+++%3D++%5Cfrac%7B+%5Csqrt%7B2%7D+-++%5Csqrt%7B3%7D++%7D%7B3+%5Csqrt%7B2%7D+-+2+%5Csqrt%7B3%7D++%7D++%5Ctimes++%5Cfrac%7B3+%5Csqrt%7B2%7D+%2B+2+%5Csqrt%7B3%7D++%7D%7B3+%5Csqrt%7B2%7D+%2B+2+%5Csqrt%7B3%7D++%7D++%5C%5C++%5C%5C++%3D++%5Cfrac%7B+%5Csqrt%7B2%7D%283+%5Csqrt%7B2%7D+%2B+2+%5Csqrt%7B3%7D++%29+-++%5Csqrt%7B3%7D%283+%5Csqrt%7B2%7D++%2B+2+%5Csqrt%7B3%7D++%29+%7D%7B+%28%7B3+%5Csqrt%7B2%7D+%7D%5E%7B2%7D%29+-+%28+%7B2+%5Csqrt%7B3%7D+%7D%5E%7B2%7D%29++%7D++%5C%5C++%5C%5C++%3D++%5Cfrac%7B6+%2B+2+%5Csqrt%7B6%7D+-+3+%5Csqrt%7B6%7D+-+6++%7D%7B18+-+12%7D++%5C%5C++%5C%5C++%3D++%5Cfrac%7B+-++%5Csqrt%7B6%7D+%7D%7B6%7D++%5C%5C++%5C%5C+)
HOPE IT HELPS..
THANKS ^-^
Here's your answer.. ⬇⬇
HOPE IT HELPS..
THANKS ^-^
abhi569:
It should (3√2)² not (3√2²)
Similar questions